Antifungal and antimycotoxigenic activities of a synthetic zingerone-derivative 4-(4‑hydroxy-3-nitrophenyl)-2-butanone against Aspergillus flavus and Fusarium graminearum - Kwang-Soo Jung; Yubin Lee; Dariimaa Ganbat; Soo Jean Park; Sung-Eun Lee (Applied Food Research)
Fungal infections and mycotoxin contamination in agricultural products and processed foods pose a significant threat to grain safety and human health worldwide, while the emergence of fungal resistance to existing antifungal agents underscores the urgent need for new therapeutic solutions. In this study, zingerone and its 34 synthesized derivatives were evaluated for their antifungal activities against two fungal species, Aspergillus flavus and Fusarium graminearum. Among them, 4-(4‑hydroxy-3-nitrophenyl)-2-butanone (designated as ZN22), where the methoxy group of zingerone is substituted by a nitro group, exhibited the strongest antifungal activity. In vitro antifungal activities were evaluated using agar diffusion, agar dilution, and mycelial growth inhibition assays. In the agar diffusion assay, ZN22 demonstrated potent antifungal activity against F. graminearum compared to A. flavus, showing similar inhibitory effects at concentrations of 50 mg/mL and 10 mg/mL, respectively. The agar dilution assay revealed more profound antifungal activity with significant inhibition at a concentration of 200 mg/L. In addition, it effectively inhibited aflatoxin production via significant downregulation of aflatoxin biosynthesis-related genes, while it enhanced deoxynivalenol production until it completely inhibited fungal mycelial growth. In vivo assay results conducted on cherry tomato fruits were consisted with in vitro results. The percentage of disease incidence treated with ZN22 at 5000, 10,000, and 50,000 mg/L in F. graminearum group and A. flavus group were reduced for 4.98 %, 21.52 %, 55.2 % and 65.37 %, 27.97 %, 48.15 %, respectively. Altogether, ZN22 has potential as a novel preservative in the agricultural and food industries, pending further safety evaluations.